Exquisite corpses. Volume1 - Tynion, James, IV; Walsh, Michael (Comic book artist); Pichetshote, Pornsak (Image Comics, 2025)
Every five years on Halloween, the wealthiest families in America play a game. Twelve of the deadliest people in the world are dropped into a small town with just one goal: last killer standing wins. For the citizens of Oak Valley, Maine - this year's unlucky arena - the goal is much simpler. They must survive the night. --from Amazon.